Efek Mediasi Kepuasan Kerja : Dampak Work-Life Balance dan Disiplin Kerja Terhadap Kinerja Pegawai - Muhammad Rifky; Sutianingsih Sutianingsih (Universitas Slamet Riyadi, 2023)
The purpose of this research is to determine how work-life balance affects productivity in the workplace. The present study employed associative research methodologies utilising a quantitative descriptive approach. This study utilises primary data and secondary data as the two main sorts of data sources. Primary data is derived from the direct analysis or processing of the subject matter. When conducting an investigation, researchers often turn to secondary sources, such as books and archival materials, for information. According to the results of this research, there is a significant relationship between individuals' levels of job satisfaction and their ability to strike a healthy balance between their professional and personal lives. At SAMSAT Boyolali, the elements of work-life balance, work discipline, and workplace satisfaction have a significant impact on the performance of employees. It should come as no surprise that factors such as work-life balance and work discipline have a major impact on employee performance when job satisfaction plays the role of a mediator.